3D-EAUS and MRI in the Activity of Anal Fistulas in Crohn’s Disease - Maria Eleonora Alabiso; Francesca Iasiello; Gianluca Pellino; Aniello Iacomino; Luca Roberto; Antonio Pinto; Gabriele Riegler; Francesco Selvaggi; Alfonso Reginelli (Gastroenterology Research and Practice)
Aim. This study aspires to assess the role of 3D-Endoanal Ultrasound (3D-EAUS) and Magnetic Resonance Imaging (MRI) in preoperative evaluation of the primary tract and internal opening of perianal fistulas, of secondary extensions and abscess. Methods. During 2014, 51 Crohn’s disease patients suspected for perianal fistula were enrolled. All patients underwent physical examination with both the methods and subsequent surgery. Results. In the evaluation of CD perianal fistulas, there are no significant differences between 3D-EAUS and MRI in the identification of abscess and secondary extension. Considering the location, 3D-EAUS was more accurate than MRI in the detection of intersphincteric fistulas (p value = 10−6); conversely, MRI was more accurate than 3D-EAUS in the detection of suprasphincteric fistulas (p value = 0.0327) and extrasphincteric fistulas (p  value=4⊕10-6); there was no significant difference between MRI and 3D-EAUS in the detection of transsphincteric fistulas. Conclusions. Both 3D-EAUS and MRI have a crucial role in the evaluation and detection of CD perianal fistulas. 3D-EAUS was preferable to MRI in the detection of intersphincteric fistulas; conversely, in the evaluation of suprasphincteric and extrasphincteric fistulas the MRI was preferable to 3D-EAUS.